Awareness and utilization of The Essential Electronic Agricultural Library (TEEAL) by the researchers at International Institute of Tropical Agriculture (IITA) Library, Ibadan, Nigeria (2011)
This study examined the awareness and use of The Essential Electronic Agricultural Library (TEEAL) at the International Institute of Tropical Agriculture Library, Ibadan, Nigeria. Data collection was by questionnaire, using random sampling techniques. A total of forty-two (84 per cent) out of fifty responses were returned and analysed. Researchers both within and outside users are aware of the availability of the TEEAL database in the IITA library. IITA scientists and research fellows are the major users of the TEEAL database. The study also revealed that most of the users relied on the staff assistance to search and retrieve information. The major challenges to the use of TEEAL database are users' lack of information literacy skills and high cost of printing. The study recommends that user should be trained to use the database themselves. The cost of printing should be subsidised. Improve on the sustainability of current information in the agricultural research institutes in Nigeria. Recommend users self service approach.